Method and tool for measuring tensile shear bond strength of surface-bonded specimens

JP7643119B2Active Publication Date: 2025-03-11TORAY INDUSTRIES INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021047291
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-31
Filing Date
2021-03-22
Publication Date
2025-03-11
Estimated Expiration
2041-03-22

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、2枚の試験片を面接合した引張せん断試験体による接合面のせん断強さの測定において、接合面内に安定した、せん断面を生じさせることができ、さらに接合面外方向の荷重発生を抑止した測定方法および測定用治具を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643119000002
    Figure 0007643119000002
  • Figure 0007643119000003
    Figure 0007643119000003
  • Figure 0007643119000004
    Figure 0007643119000004
Patent Text Reader

Abstract

To provide a measurement method which can form a stable shear cross section in a joint face, and suppresses the generation of a load in an outer direction of the joint face, in a measurement of the shear strength of the joint face using a tensile shear specimen which is obtained by face-joining two specimens, and a measurement jig.SOLUTION: A face joint specimen is fixed to a jig along respective processes of: A. placing an end part of an upper test piece of the face joint specimen on a pedestal part of a second jig; B. placing a claw part arranged at an upper end of a first jig on an end part of a lower test piece of the face joint specimen; C. forming a jig by fastening the first jig and the second jig so as to maintain an end-opening distance; D. fixing the upper test piece of the face joint specimen and the fastened jig to a tensile tester; and E. operating the tensile tester, placing a tensile load on the face joint specimen, and measuring the tensile load until a joint part is collapsed. Tensile shear strength is thereby measured.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method and a measuring tool for measuring the tensile shear bond strength of a surface-bonded test specimen having a surface-bonded portion. In particular, the present invention relates to a method and a measuring tool for measuring the bond strength in the shear direction in a plane parallel to the tensile load with high accuracy in measuring the bond strength of a tensile shear test specimen (so-called single lap shear test specimen) consisting of two surface-bonded rectangular test pieces. [Background technology]

[0002] The shear strength of the joint of a tensile shear strength test specimen, in which two rectangular test pieces are joined by, for example, using an adhesive, is measured by attaching a backing plate to the gripping parts at both ends of the test piece as specified in JIS K6850 (1999) and performing a tensile test in the same manner as JIS K7161 (2014).

[0003] However, with this measurement method, not only is a shear load in a plane parallel to the tensile load generated, but a load in the direction that peels this plane apart is also generated, making it difficult to measure the in-plane shear strength of the bonding surface, which is what is actually being measured.

[0004] Therefore, in order to more accurately measure the tensile shear joint strength of surface-bonded specimens, measurement methods using jigs such as those disclosed in Patent Documents 1 to 3 have been proposed. However, even when these methods are used, in the measurement of tensile shear specimens in which thin test pieces such as carbon fiber composite materials are surface-bonded with an adhesive, problems such as the occurrence of a peel load whose influence on the joint surface cannot be ignored, and even if a shear load due to a tensile load is applied, the state of the fracture surface of the joint after measurement is unstable and the value of the tensile shear strength varies widely due to differences in the characteristics of the interface between the surface of the test piece and the adhesive, the characteristics of the adhesive itself, and the characteristics inside the material specific to carbon fiber composite materials.

[0005] In addition, Patent Documents 1 to 3 describe an example of a test piece gripper for tensile shear strength, but do not describe the specific dimensions of the gripper relative to the size of the joint test piece, or the method of attaching the test piece to the gripper. For example, if one operator measures test pieces with the same shape, dimensions, and rigidity using a specific measuring jig and the results are relatively compared and analyzed, no problem occurs. However, if the specifications of the test pieces are different and multiple operators use jigs that match the specifications, the measurement results will not be stable even if the measurements are made according to the methods described in Patent Documents 1 to 3, and it cannot be said that they are satisfactory for objective comparison and analysis. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2013-234909 A [Patent Document 2] Japanese Patent Application Publication No. 9-304202 [Patent Document 3] Japanese Utility Model Application Publication No. 6-28713 Summary of the Invention [Problem to be solved by the invention]

[0007] Therefore, the problem that the present invention aims to solve is to provide a measurement method and a measurement tool that can generate a stable shear surface within the joint surface when measuring the shear strength of the joint surface using a tensile shear test specimen formed by surface-bonding two test pieces, and that prevents the generation of loads in directions outside the joint surface. [Means for solving the problem]

[0008] The present inventors have found that the above problems can be solved mainly by the following configuration. (1) A method for measuring the shear strength of a joint surface by a tensile shear strength test of a surface-jointed specimen using a tensile testing machine, the surface-jointed specimen having a joint formed by surface-joining ends of a pair of test pieces consisting of an upper test piece and a lower test piece, and each test piece is arranged such that the extension directions from the end constituting the joint to the other end are opposite to each other. 、 Follow the steps below: hand A method for measuring the tensile shear bond strength of a surface-bonded test specimen, comprising measuring the tensile shear strength. A. A step of placing an end of the upper test piece of the surface-bonding test body on the base portion of the second jig B. A step of placing a claw portion provided at the upper end of a first jig and protruding in a direction perpendicular to the tensile direction of the surface-bonded test piece on the end of the lower test piece of the surface-bonded test piece while controlling the end opening distance between the tip of the claw portion and the upper test piece; C. A process of fastening a first jig and a second jig together to maintain the end opening distance to form the jig; D. Fixing the upper test piece of the surface-bonded test specimen and the fastened jig to a tensile tester; E. A process of operating a tensile testing machine, applying a tensile load to the surface joint test piece, and measuring the tensile load until the joint breaks. (2) A method for measuring the tensile shear bond strength of a surface-bonded test specimen described in (1), characterized in that in step B, a first spacer is further sandwiched between the lower test piece and the first jig. (3) A method for measuring the tensile shear bond strength of a surface-bonded test specimen described in (1) or (2), characterized in that in step A, a third spacer is further sandwiched between the upper test piece and the second jig. (4) A method for measuring the tensile shear bond strength of a surface-bonded test specimen described in any one of (1) to (3), characterized in that in step A, a second spacer is further sandwiched between the lower test piece and the second jig. (5) The method for measuring tensile shear bond strength according to any one of (1) to (4), wherein at least one test piece of the surface-bonded test specimen is made of fiber-reinforced resin. (6) The method for measuring tensile shear bond strength according to any one of (1) to (5), wherein at least one test piece of the surface-bonded test specimen is made of carbon fiber reinforced resin. (7) The method for measuring tensile-shear bond strength according to any one of (1) to (6), characterized in that the upper test piece and the lower test piece are surface-bonded via a bonding member. (8) A measuring jig for measuring the shear strength of a joint surface in a tensile shear strength test of a surface-bonded test specimen using a tensile testing machine, comprising a first jig and a second jig for fastening the surface-bonded test specimen, and a spacer, wherein the surface-bonded test specimen has a surface-bonded portion in which the ends of a pair of test specimens consisting of an upper test piece and a lower test piece are surface-bonded, and each test piece is arranged such that the extension directions from the end constituting the joint to the other end are opposite, the first jig protrudes perpendicular to the tensile direction of the surface-bonded test specimen and has a claw portion to be placed on the end face of the lower test piece, and the second jig has a base portion on which the end of the upper test piece is placed. (9) The jig according to (8), characterized in that as the spacer, a first spacer is used that is inserted between the first jig and the lower test piece and clamped therebetween. (10) The jig according to (8) or (9), characterized in that the spacer used is a second spacer that is inserted between the second jig and the lower test piece and clamped therebetween. (11) The jig according to any one of (8) to (10), wherein the spacer used is a third spacer that is inserted between the second jig and the upper test piece and clamped therebetween. Effect of the Invention

[0009] According to the present invention, in measuring the shear strength of a joint interface using a tensile shear test specimen formed by surface-bonding two test pieces, a stable shear surface can be generated within the joint interface, and a measurement method and measurement tool can be provided which prevent the generation of loads in directions outside the joint interface. [Brief description of the drawings]

[0010] [Figure 1] FIG. 11 is a cross-sectional view showing the positional relationship between a surface-bonding test specimen and a jig. [Diagram 2] This is an example of a surface joint test specimen. [Diagram 3] This is an example of a method for adjusting the position of the surface-bonding test specimen on which the claws of the first jig are hooked. [Figure 4] 1 is an example of a first jig and a second jig. [Diagram 5] This shows the opening type (mode I) of crack propagation during material failure. [Figure 6] This shows the in-plane shear type (mode II) of crack propagation during material failure. [Figure 7] This shows the out-of-plane shear type (mode III) of crack propagation during material failure. [Figure 8] This is an example of the first jig. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described in more detail below with reference to the embodiments.

[0012] The present invention relates to a method for measuring the shear strength of a joint surface by a tensile shear strength test of a surface-jointed specimen using a tensile testing machine, the surface-jointed specimen having a joint formed by surface-joining ends of a pair of test pieces consisting of an upper test piece and a lower test piece, and each test piece is arranged such that the extension directions from the end constituting the joint to the other end are opposite to each other. 、 Follow the steps below: hand This is a method for measuring the tensile shear bond strength of a surface-bonded test specimen, characterized by measuring the tensile shear strength. A. A step of placing an end of the upper test piece of the surface-bonding test body on the base portion of the second jig B. A step of placing a claw portion provided at the upper end of a first jig and protruding in a direction perpendicular to the tensile direction of the surface-bonded test piece on the end of the lower test piece of the surface-bonded test piece while controlling the end opening distance between the tip of the claw portion and the upper test piece; C. A process of fastening a first jig and a second jig together to maintain the end opening distance to form the jig; D. Fixing the upper test piece of the surface-bonded test specimen and the fastened jig to a tensile tester; E. A process of operating a tensile testing machine, applying a tensile load to the surface joint test piece, and measuring the tensile load until the joint breaks.

[0013] The surface-bonded test specimen used in the measurement of the present invention will now be described.

[0014] A surface-jointed specimen is a specimen in which the ends of a pair of specimens, an upper specimen 1 and a lower specimen 2, are joined together over a finite area, as shown in Figure 1.

[0015] Surface joining methods include adhesive bonding using adhesives, fusion joining by heating a portion of one or both of the test pieces with a laser or ultrasonic waves, etc., and melting the test pieces themselves or via a molten joining material, welding joining by dissolving a portion of one or both of the test pieces with a solvent, etc., and diffusion joining by overlapping one or both of the test pieces in a part or all state where the material is not hardened and is still fluid, and then heating or cooling to harden them after the material components have diffused into each other in the overlapping area. Surface joining is a method characterized by its ability to uniformly join wide areas, unlike methods that join at points with screws, nails, screws, etc.

[0016] At least one of the test pieces constituting the surface-bonding test specimen is preferably made of fiber-reinforced resin, which has a structure in which reinforcing fibers are impregnated with a matrix resin.

[0017] Examples of reinforcing fibers include carbon fibers and glass fibers. Of these, it is preferable to use carbon fibers because of their excellent mechanical properties and ease of designing the properties. By making a carbon fiber composite material and containing 1% by weight or more of carbon fibers in a resin, the carbon fibers adhere well to the resin forming the matrix, resulting in excellent mechanical properties.

[0018] The carbon fiber used in the present invention is preferably a polyacrylonitrile-based carbon fiber. The polyacrylonitrile-based carbon fiber is excellent in terms of realizing low cost while having a good balance of specific strength, specific rigidity, light weight, and electrical conductivity.

[0019] The resin used in the present invention may be a thermosetting resin, a thermoplastic resin, etc. Among them, from the viewpoint of mechanical properties and processing properties during molding, a thermosetting resin is preferable.

[0020] Examples of thermosetting resins that can be used include unsaturated polyester resins, vinyl ester resins, epoxy resins, phenolic resins (resol type), urea-melamine resins, polyimide resins, and copolymers, modified products, or blends of two or more of these resins.

[0021] Among these, in order to obtain a carbon fiber composite material with excellent mechanical properties, epoxy resins are preferred because they are easy to mix with thermosetting resins and reinforcing fibers and easy to mold. Among these, epoxy resins containing bisphenol A type epoxy resin as the main component are preferred from the viewpoint of economical efficiency and balance of mechanical properties. In addition, elastomers or rubber components may be added to the thermosetting resin composition to improve impact resistance.

[0022] When conducting a tensile shear strength test on a surface-bonded specimen using a tensile testing machine, when measuring a surface-bonded specimen in which at least one of the test pieces is fiber-reinforced resin as described above, the material is not homogeneous and the transmission route of the external force spans multiple points such as the fiber itself, the resin itself, and the interface between the fiber and the resin. In conventional tensile shear tests, therefore, the shear surface formed becomes unstable.

[0023] Here, the shear state of the joint surface of surface-jointed members that occurs in a tensile shear test can be classified into three modes as shown in Figures 5 to 7. Of these, the important mode in terms of joint strength is the strength of the shear state of Mode II in Figure 6. The measuring method of the present invention is aimed at measuring the shear strength of Mode II stably and with high accuracy.

[0024] In particular, when the test piece is made of carbon fiber reinforced resin, in conventional tensile shear tests, the plate thickness of the test piece made of carbon fiber reinforced resin is thin and the bending rigidity of the test piece cannot be sufficiently ensured, so bending deformation is likely to occur around the joint, and a peel load in the direction outside the shear plane acts on the joint surface, making it difficult to measure the mode II shear strength. The measurement method of the present invention solves this problem and enables good measurement.

[0025] The method for measuring the tensile shear bond strength of a surface-bonded test specimen according to the present invention will be described in detail below.

[0026] First, the step A is performed in which the end of the upper test piece of the surface-bonding test body is placed on the base of the second jig. Next, as shown in FIG. 1, the step B is performed in which the claw portion of the first jig is placed on the end of the lower test piece while controlling the end opening distance.

[0027] Then, C. the step of fastening the first jig and the second jig is carried out, followed by D. the step of fixing the jig to a tensile tester. Finally, it is important to carry out E. the step of operating the tensile tester, loading a tensile load on the surface-bonded test piece, and measuring the tensile load until the bonded part breaks.

[0028] Here, each step will be described in detail.

[0029] First, step A is performed: placing the end of the upper test piece of the surface-bonding test specimen on the pedestal of the second jig. At this time, it is important to place the upper test piece so that the entire end side surface is in contact with the pedestal, as shown in Figure 3. For example, if only a part of the end side surface, such as a corner, is in contact, the load may not be applied appropriately to the desired location during the tensile test.

[0030] The second jig used in this step has a pedestal. As shown in FIG. 4, the pedestal has a shape that protrudes in a direction perpendicular to the tensile direction, and it is important that the length of the protrusion is such that the end of the upper test piece and the entire surface joint portion can be placed on it. Furthermore, the tip of the pedestal is long enough to contact the lower test piece. With such a length, it is possible to effectively apply a tensile load to the target location. The material of the second jig is preferably a material that does not deform or break during measurement, such as metal, and does not undergo dimensional changes even when used continuously. Particularly preferred are iron and stainless steel.

[0031] Next, B. a step is performed in which a claw portion provided at the upper end of a first jig and protruding in a direction perpendicular to the tensile direction of the surface-bonded test piece is placed on the end of the lower test piece of the surface-bonded test piece while controlling the end-opening distance between the tip of the claw portion and the upper test piece. At this time, it is important to control the end-opening distance between the tip of the claw portion of the first jig and the upper test piece, as shown in Figure 1.

[0032] The control of the end opening distance will be explained in more detail with reference to the enlarged view of Fig. 1. As shown in Fig. 1, there are four patterns of the position where the claws are placed, Cases I to IV.

[0033] The first jig used in these steps will be described. As shown in Figure 1, the first jig has a gamma-shaped claw protruding in a direction perpendicular to the tensile direction. The claw is placed on the lower test piece and the joint part of the surface-bonding test specimen shown in Figure 2. By applying this claw to a specific position on the joint surface, the load of the tensile tester can be applied to the specific position on the joint surface, and the tensile shear joint strength at the specific position on the joint surface can be measured.

[0034] Case I is a case where the tensile load is transmitted to the joint surface through the lower test piece. Although the formation of the shear surface of the joint due to the tensile load is difficult to stabilize, this is close to the commonly used tensile-shear test.

[0035] In Case II or IV, a tensile load is applied directly to the interface of the joint from the jaws of the jig, forming a shear surface at the interface. In this case, the shear strength of the interface is measured, which is effective for confirming the effect of surface treatment of the test piece.

[0036] In case III, when the specimens are joined via a joining material such as an adhesive or an adhesive film, a tensile load is applied directly to the joining material from the jaws of the jig to form a shear surface in the joining material, which is effective for knowing the characteristics of the joining material used in the joining.

[0037] In this way, it is important to control the position at which the tensile load acts on the joint surface to match a predetermined position.

[0038] The material of the first jig is preferably a material such as a metal that does not deform or break during measurement and does not undergo dimensional changes even when used continuously. Particularly preferred materials are iron and stainless steel.

[0039] Next, step C is performed to fasten the first jig and the second jig together to maintain the end opening distance. At this time, the surface-joint test specimen is placed on the first jig and the second jig, which are sandwiched between them, are mechanically fastened together using bolts, screws, etc., and integrated. It is important that a load can be applied to the measurement surface for the tensile shear joint strength via the jig. The material of the bolts and screws is preferably the same as that of the first jig or the second jig.

[0040] Next, step D is performed to fix the upper test piece of the surface-bonded test specimen and the fastened jig to a tensile tester. At this time, it is important to fix the jig to the tensile tester so that the joint surface for measuring the tensile shear bond strength of the surface-bonded test specimen coincides with the axis of the tensile direction during the tensile test. If they do not coincide, a moment will act on the measurement surface during tension, making it impossible to perform appropriate measurements.

[0041] When conducting a tensile test, for example, a device can be used that has a vertically movable part (called a crosshead) built into a frame that can move in the vertical direction, and a lower base whose position is fixed, and the amount of movement of the upper movable part can be measured as the amount of movement of the crosshead, and a tensile load measuring means such as a load cell is built into the crosshead. In this case, a chuck for holding the upper test piece is provided on the crosshead side, and a fixture for fixing the fastened first and second jigs is provided on the lower base side.

[0042] Alternatively, a fixture for fixing the fastened first and second jigs may be provided on the crosshead side, and a chuck for gripping the upper test piece may be provided on the lower base side to perform the tensile test.

[0043] It is preferable to insert a universal joint between the crosshead and the jig. The use of a universal joint makes it easier to adjust the joint so that a tensile load acts in one direction.

[0044] The surface-bonded specimen is mounted on a tensile testing machine while being held by a jig, as shown in Fig. 1. Using the tensile test measuring device configured in this manner, the method for measuring tensile-shear bond strength according to the present invention is carried out as follows.

[0045] Finally, a tensile tester is operated to apply a tensile load to the surface-bonded specimen and measure the tensile load until the bond breaks. In this step, the travel distance and displacement during the test and the load at each displacement position are measured.

[0046] In step B, it is preferable to further sandwich a first spacer 6 between the lower test piece 2 and the first jig 4. By inserting the first spacer 6 between the lower test piece 2 and the first jig 4, it is possible to control the position where the claw portion is hooked, and also to suppress bending deformation of the lower test piece.

[0047] Furthermore, as shown in Figure 7, it is preferable that the vertical surface of the jaw of the first jig that faces the upper test piece has a clearance from the tip of the jaw in the direction away from the upper test piece. This clearance allows a tensile load to be applied accurately to the point where the shear strength is to be measured. It also prevents the jaw from coming into contact with the second jig and being damaged or worn out, improving measurement accuracy and reducing the variation in the measured values.

[0048] It is preferable that the surface of the jaw portion facing the end surface of the lower test piece has a perpendicularity against the tensile load with an accuracy of, for example, about 0.05 mm. Alternatively, the surface may have a relief dimension in the direction from the tip of the jaw portion away from the end surface of the lower test piece.

[0049] Furthermore, in the measurement method according to the present invention, it is preferable to adjust the thickness of the first spacer so that the gap between the first jig and the first spacer is within a range of 0 to 0.1 mm.

[0050] Furthermore, in the measurement method according to the present invention, the respective gaps between adjacent spacers and the jig, and between adjacent spacers and the test piece, are preferably in the range of 0 to 0.7 mm, and more preferably 0 to 0.1 mm.

[0051] By controlling the gap in this manner, the load generated in the out-of-plane direction of the joint surface is suppressed, and the direction in which the tensile load is introduced into the test specimen is uniquely the in-plane shear direction.

[0052] The first spacer is preferably made of a material such as a metal that does not deform or break during measurement and has high accuracy in thickness and dimensions. It is also preferable that the material does not change in dimensions even when used continuously. Particularly preferable materials are iron or stainless steel.

[0053] In step A, it is preferable that a third spacer is further sandwiched between the upper test piece and the second jig.

[0054] By inserting the third spacer 8 between the upper test piece 1 and the second jig 5, the position where the claw portion is hooked can be controlled, and bending deformation of the upper test piece can also be suppressed.

[0055] The third spacer is preferably made of a material such as a metal that does not deform or break during measurement and has high accuracy in thickness and dimensions. It is also preferable that the material does not change in dimensions even when used continuously. Particularly preferable materials are iron or stainless steel.

[0056] Similarly, in step A, it is also preferable to further sandwich a second spacer between the lower test piece and the second jig.

[0057] Bending deformation of the lower test piece can also be suppressed by inserting a second spacer 7 between the lower test piece 2 and the second jig 5. The thickness of the second spacer is preferably the same dimension as the length 10 of the base part of the second jig.

[0058] The second spacer is preferably made of a material such as a metal that does not deform or break during measurement and has high accuracy in thickness and dimensions. It is also preferable that the dimensions do not change even when the spacer is used continuously. Particularly preferable materials are iron or stainless steel.

[0059] In addition, the surface-bonded test specimen of the present invention is preferably a test specimen in which the upper test piece and the lower test piece are surface-bonded via a bonding member. By using the surface-bonding member, the bonded portion can have the thickness of the surface-bonding member, and when the claw portion of the first jig is hooked onto the bonded surface of the test specimen, the position can be easily adjusted.

[0060] The surface-bonding member is a material that forms a certain layer when bonding the test pieces together. Among them, adhesives, pressure sensitive adhesives, and adhesive sheets are particularly preferred because the thickness of the layer they form during bonding can be easily controlled to a certain thickness. EXAMPLES

[0061] The present invention will be described more specifically below with reference to examples.

[0062] [Method of measuring characteristics] The characteristics were measured as follows.

[0063] 1. Tensile shear bond strength Using the jig of the present invention, a tensile test was performed using an INSTRON universal testing machine 5969. The tensile test was performed at a test speed of 5 mm / min in an atmosphere of 23°C temperature and 50% RH humidity. The load at break was evaluated for n=20, and the average value was taken as the tensile shear bond strength (F). The difference between the maximum and minimum values ​​of the 20 measurements was taken as d, and the standard deviation of the 20 measurements was taken as σ. In addition, for each of the 20 measurements, visual observation was performed to determine the fracture state of the bond.

[0064] 2. Destruction state of the joint When measuring the tensile shear joint strength, the state of fracture of the joint was observed and classified as follows, which are shown as a, b, c, and e in Table 1. a. Cohesive failure of adhesive: This refers to the state in which the adhesive remains adhered to both test pieces at the bonding surfaces of the failed test specimen after the tensile test. b. Peeling off at the interface between the lower test piece and the bonding material...This refers to a state in which, for a test specimen that is destroyed after the tensile test, all of the bonding material remains attached to the upper test piece, and no bonding material is attached to the lower test piece. c. Peeling off at the interface between the upper test piece and the bonding material...This refers to a state in which, for a test specimen that is destroyed after the tensile test, all of the bonding material remains attached to the lower test piece, and no bonding material is attached to the upper test piece. e. Base material failure of the lower or upper test piece: This refers to the state in which the test piece itself is broken after the tensile test. The state of failure can be when the test piece buckles or collapses, or when the outermost layer of the joint surface of the test piece peels off.

[0065] The fracture surface of each surface-jointed test specimen was observed, the fracture state of each specimen was identified, and the frequency of occurrence of each fracture state among all 20 tests was calculated. Frequency of occurrence of destruction state (%) = (number of occurrences of the destruction state in question / 20) x 100

[0066] In addition, when observing the fracture surface of a single surface-bonded test specimen, if multiple fracture states were found, the fracture state that occupied the largest area of ​​the joint was determined to be the fracture state of that surface-bonded test specimen.

[0067] 3. Evaluation of the accuracy of tensile shear bond strength measurement Based on the frequency of occurrence of fracture at the joint, the measurement accuracy of the tensile shear joint strength was evaluated as follows. Evaluation ○: When the occurrence frequency of the most frequently occurring destruction state is between 50% and 100%. Rating ×: When the occurrence frequency of the most frequently occurring destruction state is between 0% and 50%

[0068] [Preparation of surface joint test specimens] <Carbon fiber reinforced resin 1 test piece> Sixteen sheets of unidirectional carbon fiber prepregs (P3832S-20 manufactured by Toray Industries, Inc.) were laminated with the fiber direction all aligned, and polypropylene films ("Treyfan" (registered trademark) BO2500 manufactured by Toray Industries, Inc.: thickness 50 μm, glossy type) were placed on both surfaces of this laminate, and then carbon fiber reinforced resin test pieces 1 with an average thickness of 2 mm were obtained by press molding. Then, each molded product was cut into a rectangular piece of 100 mm in length × 25 mm in width.

[0069] <Metal piece 1> Steel: Grade SPCC-SD (JIS G 3141) (thickness 2 mm) was cut using a laser to a length of 100 mm and a width of 25 mm, and then the surface of the rectangular piece was degreased with acetone to obtain metal piece 1.

[0070] <Adhesive 1> 3M's two-liquid curing epoxy adhesive "Automix" (registered trademark) Panel Bond 8115 was used as the bonding material. The adhesive was applied to the test piece using a dedicated hand gun (3M's "Automix" (registered trademark) hand gun 8117) and a dedicated mixing nozzle (3M's "Automix" (registered trademark) mixing nozzle 8193). A steel wire with a diameter of 0.5 mm was placed at the application location, and the application thickness of adhesive 1 was controlled to 0.5 mm.

[0071] In order to control the bonding area (length 12.5 mm, width 25 mm), masking paper was used around the area where the adhesive was applied for each test piece to prevent the adhesive from adhering to more than the desired area.

[0072] Adhesive 1 was applied to a predetermined position on carbon fiber reinforced resin piece 1 and a predetermined position on metal piece 1, and the two test pieces were overlapped without any misalignment between the adhesive-coated parts, and then the adhesive was cured while applying pressure to create surface-bonded test piece 1 (Fig. 2), which was then stored in an atmosphere of 25°C and 50% RH. When measuring the tensile shear bond strength, the carbon fiber reinforced resin piece 1 was attached to a jig as the lower test piece and the metal piece 1 was attached to the upper test piece, and a tensile test was performed within one week of creating the surface-bonded test piece.

[0073] Example 1 For the surface-bonding specimen 1, the third spacer thickness was 2.2 mm, the first spacer thickness was 4.4 mm, and the second spacer thickness was 5.2 mm. The specimen was attached to a jig so that the tips of the claws of the jig were engaged with the carbon fiber reinforced resin 1, and a tensile test was performed. The fracture mode and tensile shear bond strength were as shown in Table 1.

[0074] Example 2 For the surface-bonding test specimen 1, the third spacer thickness was 2.2 mm, the first spacer thickness was 3.4 mm, and the second spacer thickness was 5.2 mm. The test specimen was attached to a jig so that the tip of the claw of the jig was placed at the interface between the carbon fiber reinforced resin 1 and the adhesive 1, and a tensile test was performed. The fracture mode and tensile shear bond strength were as shown in Table 1.

[0075] Example 3 For surface-bonding specimen 1, the third spacer was 2.2 mm thick, the first spacer was 3.2 mm thick, and the second spacer was 5.2 mm thick. The specimen was attached to a jig so that the tips of the claws of the jig were placed on one layer of adhesive, and a tensile test was performed. The failure mode and tensile shear bond strength were as shown in Table 1.

[0076] Example 4 For the surface-bonding test specimen 1, the third spacer thickness was 3.2 mm, the first spacer thickness was 2.2 mm, and the second spacer thickness was 5.2 mm. The test specimen was attached to a jig so that the tip of the claw of the jig was placed over the interface between adhesive 1 and metal 1, and a tensile test was performed. The fracture mode and tensile shear bond strength were as shown in Table 1.

[0077] Example 5 For the surface-bonding specimen 1, the third spacer thickness was 2.7 mm, the first spacer thickness was 4.4 mm, and the second spacer thickness was 5.2 mm. The specimen was attached to a jig so that the tips of the claws of the jig were engaged with the carbon fiber reinforced resin 1, and a tensile test was performed. The fracture mode and tensile shear bond strength were as shown in Table 1.

[0078] Comparative Example 1 For surface-bonded specimen 1, a test pair was attached to a jig with a third spacer thickness of 2.2 mm, a first spacer thickness of 1.0 mm, and a second spacer thickness of 5.2 mm, and a tensile test was conducted. The fracture mode and tensile shear bond strength were as shown in Table 1.

[0079] [Table 1] [Industrial Applicability]

[0080] The measurement method and tool of the present invention are applicable to various materials having different test piece thicknesses and rigidity, and to all surface-jointed specimens formed by various surface-joining methods, and are particularly effective for measuring specimens made of fiber-reinforced resin, especially carbon fiber-reinforced resin.

[0081] By using the measurement method of the present invention, it is possible to simply measure the tensile shear bond strength at a specific position on the bond surface. This makes it possible to perform highly accurate structural design and calculations when designing a structure including the bonded portion, resulting in a more efficient design and reduced costs. [Explanation of symbols]

[0082] 1. Upper test piece 2. Lower test piece 3. Joining materials 4. First jig 5. Second jig 6. First spacer 7. Second spacer 8.Third spacer 9. Length of the jaws of the first jig 10. Length of the base of the second jig

Claims

1. A method for measuring the shear strength of a joint surface by conducting a tensile shear strength test on a surface-bonded specimen using a tensile testing machine, wherein the surface-bonded specimen has a joint where the ends of a pair of specimens consisting of an upper test piece and a lower test piece are surface-bonded, and each test piece is arranged so that the extension directions from the end constituting the joint to the other end are opposite, the tensile shear strength is measured according to the following steps, and in step B, a first spacer is further sandwiched between the lower test piece and a first jig. A. A step of placing an end of the upper test piece of the surface-bonding test body on the base of the second jig. B. A step of placing a claw portion provided at the upper end of the first jig and protruding in a direction perpendicular to the tensile direction of the surface-bonded test piece on the end of the lower test piece of the surface-bonded test piece while controlling the end opening distance between the tip of the claw portion and the upper test piece; C. A step of fastening the first jig and the second jig together to maintain the end opening distance, D. Fixing the upper test piece of the surface-bonded test specimen and the fastened jig to a tensile tester; E. A process of operating a tensile tester, applying a tensile load to the surface-bonded test piece, and measuring the tensile load until the bonded portion breaks.

2. A method for measuring the tensile shear bond strength of a surface-bonded specimen as described in claim 1, characterized in that in step A, a third spacer is further sandwiched between the upper test piece and the second jig.

3. A method for measuring the tensile shear bond strength of a surface-bonded test specimen as described in claim 1 or 2, characterized in that in step A, a second spacer is further sandwiched between the lower test piece and the second jig.

4. The tensile shear bond strength measuring method according to any one of claims 1 to 3, wherein at least one test piece of the surface-bonded test specimen is made of fiber-reinforced resin.

5. The tensile shear bond strength measuring method according to any one of claims 1 to 4, wherein at least one of the test pieces of the surface-bonded test specimen is made of carbon fiber reinforced resin.

6. The method for measuring tensile shear bond strength according to any one of claims 1 to 5, characterized in that the upper test piece and the lower test piece are surface-bonded via a bonding member.

7. A measuring jig for measuring the shear strength of a joint surface in a tensile shear strength test of a surface-bonded test specimen using a tensile testing machine, the measuring jig being composed of a first jig and a second jig for fastening the surface-bonded test specimen, and a spacer, the surface-bonded test specimen having a surface-bonded portion in which the ends of a pair of test specimens consisting of an upper test piece and a lower test piece are surface-bonded via a bonding member, and each test piece is arranged such that the extension direction from the end constituting the joint to the other end is opposite, the first jig protrudes perpendicular to the tensile direction of the surface-bonded test specimen and has a claw portion for being placed on the end face of the lower test piece, the second jig has a base portion for placing the end of the upper test piece on, and the measuring jig is characterized in that at least a first spacer is used as the spacer, which is inserted between the first jig and the lower test piece and clamped therebetween.

8. 8. The measuring jig according to claim 7, further comprising a second spacer that is inserted between the second jig and the lower test piece and supported therebetween.

9. 9. The measuring jig according to claim 7, further comprising a third spacer that is inserted between the second jig and the upper test piece and holds them together.

Citation Information

Patent Citations

  • Stress Applicator for Adhesion Measurement

    JP1994028713U

  • Testing jig for bonding strength

    JP1997304202A

  • Bonding strength measurement method

    JP2013234909A